Undergoing the experiences of the COVID-19 pandemic as ruptures in American civil society create conditions for right action. Issue 6 (1st November 2020) - Nicolaides, Aliki; Lim, Ahreum
ABSTRACT: The global pandemic known as COVID-19 has brought most cities and counties to a slow dance of shelter-in-place and stay-at-home curfews. This is our first personally experienced civilization-wide transformation. Nothing will return to how we knew it. The complexity of this moment—the full vitality of the unknown—is an essential feature of transformation and demands an ongoing process of moving underneath the experience of the unknown to generate right action. In this article, we will write from our own experience of COVID-19 and the rupture of civil unrest in the wake of the murder of George Floyd, Breonna Taylor, and Ahmaud Arbery. We believe that the global pandemic, and the potential of this moment in America to overcome and defeat racial disparity, suggests a space for the forging of deeper stories—stories that peel back the felt sense and fullness of a present unfolding experience. We will discuss living through these experiences as the basis for exploring the potential for the transformation of sense-making that may generate a multiplicity of new learning and new action.